BASIC INPUT CIRCUIT DESIGN WITH MEDIATOR TO USE THE LANGUAGE C 8255 PPI - Ryan Adtrianshah; Nenny Anggraini. Skom. MT (Jurnal Sistem Komputer, 2006)
Combination "Design Series Basic Input With PPI 8255 Intermediary Language Using C", a series composed of PCs, interface 8255, and a series of basic input modules that are interconnected with one another. 8255 PPI serves to mediate between the computer with the Combination the basic inputs. Combination of this function to enter data in the form of binary numbers and then output the results can be viewed on a computer screen in the form of decimals. For data processing in this circuit using the language C.